KNOWLEDGE, NUTRITIONAL STATUS AND DIET AS FITNESS OF FACTORS FOR DAVID FC FOOTBALL ATHLETES - Carrissima, Ikken Permata; Sari, Indah Purnama; Arinda, Ditia Fitri (Universitas Negeri Medan, 2025)
Soccer is a popular sport that requires optimal physical fitness, including nutritional knowledge, nutritional status, and proper diet. This study focuses on analyzing the profile of nutritional knowledge, nutritional status, and diet on the physical fitness of David FC soccer athletes. The method used was descriptive qualitative with a population of soccer athletes at David FC, using a semi-structured interview approach as well as anthropometric data. The results revealed that the majority of athletes had moderate nutritional knowledge, with normal nutritional status based on IMT/U. The analyzed diet showed an imbalance in macro and micro nutrient intake. The relationship between good nutritional knowledge and physical fitness status was found to be significant, especially in improving athletes' endurance and performance. The study's conclusions emphasize the importance of more in-depth nutrition education and structured dietary management to support the fitness and performance of soccer athletes. The findings are expected to contribute to the development of more effective athlete nutrition programs.